Immune Imbalances in Non-Alcoholic Fatty Liver Disease: From General Biomarkers and Neutrophils to Interleukin-17 Axis Activation and New Therapeutic Targets - Paquissi, Feliciano Chanana (Frontiers in Immunology, 2016)
Nonalcoholic fatty liver disease (NAFLD) is an increasing problem worldwide and is associated with negative outcomes such as cirrhosis, hepatocellular carcinoma, insulin resistance, diabetes, and cardiovascular events. Current evidence shows that the immune response has an important participation driving the initiation, maintenance, and progression of the disease. So, various immune imbalances, from cellular to cytokines levels, have been studied, either for better compression of the disease pathophysiology or as biomarkers for severity assessment and outcome prediction. In this article, we performed a thorough review of studies that evaluated the role of inflammatory/immune imbalances in the NAFLD. At the cellular level, we gave special focus on the imbalance between neutrophils and lymphocytes counts (the neutrophil to lymphocyte ratio [NLR]), and that which occurs between T helper 17 (Th17) and regulatory T cells (Treg) as emerging biomarkers. By extension, we reviewed the reflection of these imbalances at the molecular level through proinflammatory cytokines including those involved in Th17 differentiation (IL-6, IL-21, IL-23, and transforming growth factor-beta [TGF-β]), and those released by Th17 cells (IL-17A, IL-17F, IL-21, and IL-22). We gave particular attention to the role of IL-17, either produced by Th17 cells or neutrophils, in fibrogenesis and steatohepatitis. Finally, we reviewed the potential of this pathways as new therapeutics targets in NAFLD.